New atrial fibrillation and syncope in a collegiate athlete immediately following COVID-19 vaccination - Parker, W.; Joseph, S. J.; Saloni, L.; Singh, T. (Journal of the American College of Cardiology, 2022)
Background: Atrial fibrillation (AF) is a common arrhythmia in athletes with endurance athletes (high-intensity, high-volume training) at greater risk. Proposed mechanisms include atrial dilation, autonomic activation, and vagal tone. Here we describe a case of AF in an athlete after SARS-CoV-2 (COVID-19) vaccination. Case: A 20-year-old female collegiate long-distance runner with no medical history presented with palpitations and syncope 15 minutes after receiving Moderna COVID-19 vaccine dose #1. Initial rhythm was AF with rapid ventricular response (RVR) at 150 beats per minute. She spontaneously cardioverted to normal sinus rhythm (NSR) shortly thereafter, though developed prolonged exertional intolerance for several months. Electrophysiological study (EPS) demonstrated no accessory pathway, though AF with RVR recurred during her EPS and required electrical cardioversion. 2-week ambulatory rhythm monitoring showed NSR with no recurrent AF. Cardiopulmonary stress testing revealed above average peak rate of oxygen uptake (VO2) of 48.1 ml/kg/min (134% predicted), appropriate cardiopulmonary response to exercise, and no ECG changes. TSH, iron studies, CBC, and cardiac biomarkers were normal. Decision-making: While it is unclear why this patient developed AF post-vaccination, the temporal correlation suggests a causal relationship. A possible mechanism is vaccine-triggered autonomic activation. Her exertional intolerance post-vaccination may have been a consequence of autonomic dysfunction - as seen in post-COVID syndrome and isolated case reports post-vaccination - versus deconditioning from prolonged detraining. Assessing risk of recurrence with a second Moderna dose was a challenge given the paucity of data. Thus, the patient declined the second dose. While she may be predisposed to future episodes of AF as an endurance athlete, this should not limit her return to exercise. We advised a graded exercise protocol for return to sports participation. Conclusion: More data is needed to investigate a potential causal relationship between COVID-19 vaccination and AF in athletes. Importantly, this rare case should not cause hesitation in athletes considering vaccination.